Electronic Contact Lens: A Platform for Wireless Health Monitoring Applications. (28th February 2020) - Yuan, Mengyao; Das, Rupam; Ghannam, Rami; Wang, Yinhao; Reboud, Julien; Fromme, Roland; Moradi, Farshad; Heidari, Hadi
Abstract : Electronic contact lenses are used for noninvasively monitoring vital human signs and medical parameters. However, maintaining a secure communications connection and a self‐sustainable power source are still looming challenges. Herein, a proof‐of‐concept electronic contact lens is demonstrated that includes a spiral antenna with its wireless circuit unit for data telemetry, a rectifier circuit for power conditioning, and a micro‐light‐emitting diode (μLED) as a load. The spiral antenna with its rectifying circuit is designed considering operation in the industrial, scientific, and medical (ISM) band of 2.4 GHz. The spiral coil with an inner diameter of 10 mm, an outer diameter of 12 mm, and a wire width of 0.2 mm is fabricated on a donut‐shaped flexible polyimide substrate. For biocompatibility purposes, polyimide is used as the contact lens substrate and polydimethylsiloxane (PDMS) is used for encapsulation. A 3D‐printed eye model is developed for accurately shaping the curvature of the PDMS‐encapsulated contact lens. The reflection coefficient ( S 11 ) of the fabricated antenna is tested in different conditions and on an eye model to mimic the liquid condition of the human eye. In a wide range of conditions, a minimum of −20 dB reflection coefficient ( S 11 ) is obtained. Abstract : Electronic contact lenses are used for noninvasively monitoring vital human health signs. Herein, a proof‐of‐concept electronic contact lens is demonstrated that includes a wireless circuit unit with a spiral antenna (operating at 2.4 GHz with maximum gain of −28 dBi) for data telemetry, a rectifier circuit for power conditioning, and a micro light emitting diode as a load.